2019
DOI: 10.1097/spv.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Readability: Are Urogynecologic Patient Education Materials at an Appropriate Reading Level?

Abstract: Objective The National Institutes of Health recommends readability of patient material not exceed sixth-grade level. Our aim was to determine readability of American Urogynecologic Society (AUGS) and International Urogynecological Association (IUGA) patient education documents. Methods Available English- and Spanish-language IUGA patient information leaflets and AUGS patient fact sheets were scored for grade reading level. Readability assessment was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…During public health emergencies, the public needs easy access to health information that is clear, meaningful, and actionable. Our results are similar to those of previous assessments of health information (Davis et al, 1990;Stossel et al, 2012;Haller et al, 2019;Prince et al, 2019) and suggest that even during a high-stakes public health threat, deficiencies in the quality of consumer health information are common. This is especially concerning given that people in high-risk categories for limited health literacy (e.g., older adults, people with chronic health conditions, and minorities) are also the people at high risk of experiencing the worst effects of COVID-19.…”
Section: Public Health Impactsupporting
confidence: 91%
“…During public health emergencies, the public needs easy access to health information that is clear, meaningful, and actionable. Our results are similar to those of previous assessments of health information (Davis et al, 1990;Stossel et al, 2012;Haller et al, 2019;Prince et al, 2019) and suggest that even during a high-stakes public health threat, deficiencies in the quality of consumer health information are common. This is especially concerning given that people in high-risk categories for limited health literacy (e.g., older adults, people with chronic health conditions, and minorities) are also the people at high risk of experiencing the worst effects of COVID-19.…”
Section: Public Health Impactsupporting
confidence: 91%
“…This study supports the work of previous authors who cite a need for healthcare providers to address problems associated with low health literacy [ 15 - 24 , 27 ]. The findings of this study are also consistent with prior studies assessing educational materials used by other medical and rehabilitation specialties, which found that PEM are written at a higher reading level than that at which the average American can read and that is recommended by major national health organizations [ 15 - 18 ]. Finally, the findings support the work of previous authors who found that steps can be taken to reduce the reading level of PEM and that improving clients’ ability to understand healthcare materials is a multifactorial process [ 23 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…There is strong evidence to suggest that the levels of literacy required to access both written and online uro‐gynaecology and gynaecology educational materials are above the recommended reading ability (Haller et al, 2019; Reagan et al, 2015; Samuel et al, 2019; Stewart et al, 2019). Designers of educational health materials may benefit from using novel approaches such as video (Hodges‐Wills et al, 2021) or virtual reality (van der Kruk et al, 2022) incorporating consumer input to address inequities in provision of health information.…”
Section: Discussionmentioning
confidence: 99%